Trauma-Informed Care-Based Christian Education Model For Child Victims Of Domestic Violence In Christian Families (International Journal of Economics Management and Social Science, 2026)
Domestic violence in Christian families remains a deeply troubling yet often hidden phenomenon, with children bearing profound psychological, spiritual, and developmental consequences. Despite increasing awareness of trauma's impacts, Christian education (Pendidikan Agama Kristen/PAK) in Indonesian contexts has rarely integrated trauma-informed approaches, potentially re-traumatizing vulnerable children through insensitive pedagogical practices. This research develops and evaluates a trauma-informed care-based Christian education model specifically designed for child victims of domestic violence in Christian families. Using design-based research methodology, this study involved collaborative development with trauma specialists, pastoral counselors, and PAK educators, followed by implementation with twenty-eight children aged eight to twelve from three church-based support programs in North Sumatera. The developed model integrates six core trauma-informed principles: safety, trustworthiness and transparency, peer support, collaboration and mutuality, empowerment and choice, and cultural humility. These principles were operationalized through specific pedagogical strategies including establishing physical and emotional safety, using predictable routines, offering meaningful choices, validating children's experiences, addressing theological questions emerging from trauma, and reframing harmful biblical interpretations that perpetuate abuse. Data collected through classroom observations, interviews with children and caregivers, trauma symptom assessments, and analysis of children's theological expressions revealed significant outcomes. Children demonstrated decreased trauma symptoms, increased sense of safety in educational settings, more positive God-images, enhanced capacity for emotional regulation, and deeper theological understanding that integrated their lived experiences. The model also facilitated disclosure of abuse, connection with support resources, and shifts in harmful theological beliefs. However, implementation faced challenges including educator resistance to addressing trauma explicitly, institutional fears about liability, tension between therapeutic and educational objectives, and the need for extensive training. This research contributes a theoretically grounded, empirically tested framework for trauma-sensitive Christian education, offering practical guidance for churches, schools, and ministries serving traumatized children while advancing theological reflection on how faith communities can embody healing presence for the most vulnerable. Keywords: trauma-informed care; Christian education; domestic violence; child abuse; theological pedagogy; PAK; pastoral care